MODERN APPROACHES TO THE IMPROVEMENT OF THE INSTITUTE OF PAID MEDICAL SERVICES IN RUSSIA - A. V. Panov; T. Yu. Bykovskaya (Исследования и практика в медицине)
The article pertains the main problems faced by manufacturers and consumers of paid medical services. The increase in the volume of paid medical care prevails in the fields of dentistry, diagnostics and cosmetology. Of course, the expansion of voluntary medical insurance in almost all areas of medicine, further digitalization and gradual development of commercial outpatient care will be promising areas in the domestic health care. After all, currently every fourth outpatient medical organization is private owned. In this regard, taking into account the foreign and domestic experience of modernization of the medical services market, the paper comprehensively analyzes the trends in the development of commercial medicine within the legal, organizational and socio-economic regulation of the health care industry. Marketing tools to optimize the system of paid services are presented. The key role of mechanisms of public-private interaction in health care management is proved. Integrative approaches to the problems of introduction and development of paid medical services, considered in this study, will allow to systematize and to adjust the extra-budgetary activities of medical organizations while simultaneously increasing the availability and quality of medical care in Russia.